Are Managers Motivated to Explore in the Face of a New Technological Change? The Role of Regulatory Focus, Fit, and Complexity of Decision‐Making - Ahmadi, Saeedeh; Khanagha, Saeed; Berchicci, Luca; Jansen, Justin J. P. (Journal of Management Studies, 2017)
AbstractWe develop a psychological perspective on managers’ exploration orientation. Our study suggests that the regulatory focus of managers may in different ways, impact their orientation toward search, risk‐taking, and experimentation. Moreover, we argue that these relationships are contingent not only on the extent to which the organizational context fits with the motivational disposition of managers, but also on the complexity of decision‐making. Using an experimental setting, we find that managers’ regulatory focus affects their willingness to experiment with a wide range of alternatives and to deviate from existing best practices. Moreover, the promotion focus of managers heightens their exploration orientation in an organizational context with promotion‐focused cues in highly complex decision‐making. This study has important implications for our understanding of managers’ exploration orientation under conditions of complexity.